Analisis Hubungan Budaya Organisasi dengan Komitmen Organisasional Perawat Rawat Inap di Rumah Sakit Islam Sultan Agung Semarang - Fachrudin, Nur Millati Hanifah; Arso, Septo Pawelas; Fatmasari, Eka Yunila; Sriatmi, Ayun (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Organizational culture is often used as one of the determinants of tools and keys to success or failure of an organizational strategy achievement. Another thing that is closely related to organizational culture is organizational commitment. The harmony of goals achieved between employees and organizations through culture will build an organizational commitment in the employee. The purpose of this study was to determine the related of organizational culture variables with organizational commitments of inpatient nurse at Sultan Agung Islam Hospital. The method of this research was using explanatory research with cross sectional approach. The population was all nurses in inpatients unit at Sultan Agung Islam Hospital with 70 people as sample. The analysis of the data was employed univariate and bivariate analysis with Rank Spearman test. The results obtained all independent variables related with the dependent variable. The independent variables related to the commitment of the organization of inpatient nurses at Sultan Agung Islam Hospital and have strong relation strength are innovation and risk taking courage (p value 0,001 and rs = 0,584) and aggressiveness (p value 0,001 and rs = 0,500) while the independent variable related to organizational commitment and have weak relation strength is attention to detail (p value 0,018 and rs = 0,281), orientation to result (p value 0,001 and rs = 0,472), human orientation (p value 0,005 and rs = 0,335), team orientation (p value 0,001 and rs = 0,465) and stability (p value 0,001 and rs = 0,425).